New Indication for an Established Procedure: Cervical Cerclage for Prevention of Umbilical Cord Prolapse. (March 2023) - Petrikovsky, B. M.; Terrani, M.; Dillon, A.
Objective: Funic presentation is a risk factor for umbilical cord prolapse. In the majority of cases, umbilical cord prolapse is an obstetric emergency. Currently there is no strategy to prevent umbilical cord prolapse in patients with funic presentation. Placing a third trimester cervical cerclage was proposed, as a mechanical barrier of prolapse, in women with funic presentation. Materials and Methods: Twelve patients with funic presentation, detected between 23 and 34 weeks of gestation, were included in the study. Patients were informed that although cervical cerclage have been widely used in obstetrics, it had not been offered in patients with funic presentation. Gestational age at delivery, mode of delivery, location of umbilical cord at birth, presence or absence of umbilical cord prolapsed, and neonatal condition at birth were recorded in all cases. Results: Patients' age varied from 21 to 40 years, mean of 28 ± 6.2 years, and gestational age at the time of diagnosis of funic presentation varied from 26 to 34 weeks of pregnancy. All patients were seen weekly after the cervical cerclage placement to assess the umbilical cord location. Seven patients had vertex presentation, four had breech presentation, and one had transverse lie presentation. A follow-up sonogram of the umbilical cord revealed the following: funic presentation was persistent throughout the entire pregnancy in five patients, disappeared in four, and became intermittent in three. The delivery mode was as follows: cesarean section was performed in eight patients (five with persistent funic presentation, two with intermittent, and one with resolved funic presentation because of failure to progress in labor). There were five patients who delivered vaginally. Funic presentation was confirmed in all patients who underwent cesarean sections. None of the patients had had an umbilical cord prolapse. Conclusion: In view of high perinatal mortality of umbilical cord prolapses, placement of cervical cerclage could be added to obstetric armamentarium in patients with funic presentation, after proper counseling.